Adding Multiple Enzymes to Diets Containing Wheat Distillers Dried Grains with Solubles Improves Broiler Performance by Reducing Viscosity - Gouran, B.; Khorshidi, K. J.; Gharahveysi, S. (Tropical Animal Science Journal, 2025)
This study aimed to investigate the effects of adding the multienzyme Apsazyme (glucanase, xylanase, galactosidase, mannanase) to diets containing different levels of wheat distiller’s dried grains with solubles (WDDGS) on performance, ileal bacteria, intestinal viscosity, pH, and blood variables of broiler chickens. For this purpose, 300 one-day-old male and female broilers of the Ross 308 strain were used. The experimental diets included three levels of WDDGS (0%, 10%, and 20%) with and without multienzyme (125 g/ton). Data analysis was done using SAS statistical software as a factorial design. The use of 20% WDDGS reduced feed intake (FI) in the finisher period and total period compared to the control treatment (p